2012
DOI: 10.1007/s10388-012-0356-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of peritumoral mast cells in esophageal squamous cell carcinoma with neoadjuvant chemoradiotherapy

Abstract: Background Neoadjuvant chemoradiotherapy (CRT) followed by surgery is the standard approach for locally advanced esophageal cancer. Recently, the microenvironment (including the host immune response) after conventional chemo-and/or radiotherapy has been highlighted. The aim of this preliminary study was to evaluate peritumoral mast cells (MCs) in esophageal squamous cell carcinoma (ESCC) after neoadjuvant CRT. Methods We obtained a total of twenty specimens from patients with ESCC who underwent neoadjuvant CRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Previous researches have reported that TIMs might kill tumor cells and enhance the effect of chemotherapy [ 24 , 25 ]. Therefore, we estimated the benefit of gemcitabine-based chemotherapy according to the level of TIMs in patients who received adjuvant chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Previous researches have reported that TIMs might kill tumor cells and enhance the effect of chemotherapy [ 24 , 25 ]. Therefore, we estimated the benefit of gemcitabine-based chemotherapy according to the level of TIMs in patients who received adjuvant chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…We previously recorded the numbers of peritumoral CD8-and Foxp3-positive cells using light microscopy and the median count was calculated for each sample. The median values for the number of CD8-and Foxp3-positive cells were 70 (range, 18-250) at a magnification x200 and 13 (range, 1-57) at a magnification x100 (18). We analyzed the correlation of Fas/FasL expression with peritumoral CD8-and Foxp3-positive cells.…”
Section: -Fluorouracilmentioning
confidence: 99%